2016
DOI: 10.1165/rcmb.2015-0237oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α Regulates CD55 in Airway Epithelium

Abstract: Airway epithelial CD55 down-regulation occurs in several hypoxia-associated pulmonary diseases, but the mechanism is unknown. Using in vivo and in vitro assays of pharmacologic inhibition and gene silencing, the current study investigated the role of hypoxia-inducible factor (HIF)-1α in regulating airway epithelial CD55 expression. Hypoxia down-regulated CD55 expression on small-airway epithelial cells in vitro, and in murine lungs in vivo; the latter was associated with local complement activation. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…While these studies have been important in showing how CRPs can be upregulated in cultured cells in hypoxic conditions, they cannot replicate the complex in vivo milieu of a rejecting transplant [47]. Inverse correlation of tissue expression of active complement components and CRPs have been crucial to the progress of transplant injury and associated tissue remodeling during rejection [48][49][50]. The key hypothesis to be tested in this manuscript is that during alloimmune inflammation, graft microvasculature and the airway epithelium is rendered susceptible to complement-mediated injury through decreased expression of major complement regulatory protein CD55 during a mouse model of OTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these studies have been important in showing how CRPs can be upregulated in cultured cells in hypoxic conditions, they cannot replicate the complex in vivo milieu of a rejecting transplant [47]. Inverse correlation of tissue expression of active complement components and CRPs have been crucial to the progress of transplant injury and associated tissue remodeling during rejection [48][49][50]. The key hypothesis to be tested in this manuscript is that during alloimmune inflammation, graft microvasculature and the airway epithelium is rendered susceptible to complement-mediated injury through decreased expression of major complement regulatory protein CD55 during a mouse model of OTT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well reported that HIF-1α, as the master regulator of oxygen homeostasis, is an important modulator of the tissue repair phase through its signaling in cell migration, cell survival, cell division, growth factor release, and matrix synthesis during the repair [56,57]. In addition, hypoxia results in tissue ischemia and the expression of a pro-inflammatory state through the downregulation of complement regulatory protein, CD55 [50]. The crucial role of pathological remodeling during persistent inflammation in small airways has been reported in both preclinical and clinical transplantation data, which obstruct the regeneration of airway epithelium and promote fibro-proliferation due to aberrant tissue repair [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“… + ND Cell line, primary cell [ 25 , 152 , 292 , 320 , 330 , 331 ] ? + Apical Cell line, intestinal loop [ 190 , 292 ] CD55 + + ND Cell-free system, cell line [ 294 296 , 332 ] + + Apical Cell-free system, cell line [ 193 , 294 296 , 333 ] CD172α (SIRPα) ? a ND [ 25 ] + a Lateral Cell line [ 161 ] JAM-A (CD321) ?…”
Section: Transepithelial Migration (Tepm)mentioning
confidence: 99%
“…In addition to H/R, consecutive hypoxia for a long period has also been reported to modulate the inflammatory functions and oxidant-induced cell injury in airway epithelial cells (Olson et al, 2011;Pahlman et al, 2015;Pandya et al, 2016;Polke et al, 2017). It was shown that consecutive hypoxia for longer than 24 h contributed to the pathogenesis of chronic pulmonary diseases via both the HIF1α-dependent downregulation of the complement regulatory protein CD55 and several inflammatory cytokines, including IL-6, IP-6, IP-10, and hBD-2, as well as the TGFβ1-dependent downregulation of the secretory leukocyte protease inhibitor, in human airway epithelial cells (Pahlman et al, 2015;Pandya et al, 2016;Polke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to H/R, consecutive hypoxia for a long period has also been reported to modulate the inflammatory functions and oxidant-induced cell injury in airway epithelial cells ( Olson et al, 2011 ; Pahlman et al, 2015 ; Pandya et al, 2016 ; Polke et al, 2017 ). It was shown that consecutive hypoxia for longer than 24 h contributed to the pathogenesis of chronic pulmonary diseases via both the HIF1α-dependent downregulation of the complement regulatory protein CD55 and several inflammatory cytokines, including IL-6, IP-6, IP-10, and hBD-2, as well as the TGFβ1-dependent downregulation of the secretory leukocyte protease inhibitor, in human airway epithelial cells ( Pahlman et al, 2015 ; Pandya et al, 2016 ; Polke et al, 2017 ). Continuous exposure to hypoxia for 24 h was also reported to inhibit active sodium absorption and the HIF2α- and NF-κB-dependent bacterial infection ( Tomlinson et al, 1999 ; Schaible et al, 2013 ), while hypoxia for 12 h was shown to increase HIF1α-dependent miR-200b expression and decrease expression of the cystic fibrosis transmembrane conductance regulator (CFTR) ( Bartoszewska et al, 2017 ), and hypoxia for 6 h was sufficient to significantly ameliorate the oxidant-induced epithelial barrier dysfunction ( Olson et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%